Oestrogen treatment and N-terminal propeptide of type I collagen concentration in culture media of human pubo-cervical fascia fibroblasts surrounding polypropylene mesh used in urogynaecological surgery procedures - Tomaszewski, Jacek; Adamiak-Godlewska, Aneta; Bogusiewicz, Michał; Brzana, Wojciech; Juszczak, Małgorzata; Rzeski, Wojciech; Rechberger, Tomasz (Menopause Review/Przegląd Menopauzalny, 2010)
Objectives: Polypropylene meshes are widely used for surgical treatment of stress urinary incontinence (SUI) and pelvic organ prolapse (POP). Synthesis and deposition of collagen induced by an inserted implant are largely controlled by oestrogens. The aim of the study was to assess the rate of collagen type I (Col I) synthesis by pubo-cervical fascia (PCF) fibroblasts cultured with mono- or multifilament polypropylene meshes in the presence of oestrogens. Material and Methods: Specimens of PCF were obtained during a surgical procedure from a 56-year-old woman suffering from SUI and POP. Fibroblasts were cultured with mono- or multifilament meshes and exposed to 17β-oestradiol, oestriol or phytoestrogen daidzein. The cultures were run for 216 hrs and the media were replaced every 72 hrs. Procollagen type 1 N-terminal propeptide (PINP), a marker of Col I biosynthesis, was assessed in culture media by radioimmunoassay. Results: The biosynthesis of Col I was more abundant in the presence of monofilament than multifilament meshes. Fibroblasts exposed to oestriol or daidzein produced more Col I than those treated with oestradiol, regardless of the mesh applied. In the presence of monofilament mesh the rate of Col I synthesis induced by oestriol and daidzein increased persistently until the end of the experiment, whereas the peak concentration of PINP in cultures treated with oestradiol was observed between 72 hrs and 144 hrs. In the presence of multifilament mesh the rate of Col I production dropped after 144 hrs in all cultures. Conclusions: PCF fibroblasts produce more Col I when cultured on monofilament than on multifilament mesh. This process may be enhanced by oestriol and phytoestrogens.